2017
DOI: 10.1038/s41598-017-17664-9
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence that Knops Blood Group Polymorphisms Affect Complement Receptor 1 Clustering on Erythrocytes

Abstract: Clustering of Complement Receptor 1 (CR1) in the erythrocyte membrane is important for immune-complex transfer and clearance. CR1 contains the Knops blood group antigens, including the antithetical pairs Swain-Langley 1 and 2 (Sl1 and Sl2) and McCoy a and b (McCa and McCb), whose functional effects are unknown. We tested the hypothesis that the Sl and McC polymorphisms might influence CR1 clustering on erythrocyte membranes. Blood samples from 125 healthy Kenyan children were analysed by immunofluorescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Previously, we have shown that neither cofactor activity for the breakdown of C3b and C4b nor binding to C1q are influenced by the Sl2 and McC b mutations ( Tetteh-Quarcoo et al, 2012 ). In addition, we can find no association between Knops genotype and CR1 clustering on erythrocytes ( Paccaud et al, 1988 ; Swann et al, 2017 ). However, other potential effects such as altered immune complex binding and processing or activation of the complement lectin pathway via mannose-binding lectin ( Ghiran et al, 2000 ) have not yet been investigated.…”
Section: Discussionmentioning
confidence: 81%
“…Previously, we have shown that neither cofactor activity for the breakdown of C3b and C4b nor binding to C1q are influenced by the Sl2 and McC b mutations ( Tetteh-Quarcoo et al, 2012 ). In addition, we can find no association between Knops genotype and CR1 clustering on erythrocytes ( Paccaud et al, 1988 ; Swann et al, 2017 ). However, other potential effects such as altered immune complex binding and processing or activation of the complement lectin pathway via mannose-binding lectin ( Ghiran et al, 2000 ) have not yet been investigated.…”
Section: Discussionmentioning
confidence: 81%